PENGARUH ADANYA PARAFIN LILIN TERHADAP KARAKTERISTIK ASPAL DAN CAMPURAN BERASPAL - Tjitjik W Suroso (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Good asphalt derives from asphaltic base crude dil, but unfortmately such material is not much, asphalt from residual crude oil containing the mixture of asphaltic and parafine base is possibly used. Parafin changes easily in low different temperature. Therefore, the presence of parafin in asphalt will disturb the performance of asphalt mixture and predicted to be the reason of pvement deformation. To determine the effect of wax on asphalt rheology and mix proferties, 1-5% of solid and liquid wax can be used in asphalt. Asphalt quality and asphalt mixture can be done using Marshall test, dynamic stability by wheel tracking machine and resilient moduli by UMATTA. Research showed that wax decreased the properties of asphalt rheology in softening point differences penetration index, steffness moduli adhesion of asphalt to aggregates wax also decreased asphalt mix performance either by marshall test, dynamic stability and resilient moduli The effect of 4 % ot solid wax on asphalt in safe category, 2% of parafin influenced the adhesion of asphalt to aggreagates, the safe limit for liquid wax is 2 % it is suggested that the limit of parafin consent is 2% so that early pavement damage will not eusily happen.